2018
DOI: 10.1038/s41598-018-26049-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal plasma treatment improves chicken sperm motility via the regulation of demethylation levels

Abstract: The quality of avian semen is an important economic trait in poultry production. The present study examines the in vitro effects of non-thermal dielectric barrier discharge plasma on chicken sperm to determine the plasma conditions that can produce the optimum sperm quality. Exposure to 11.7 kV of plasma for 20 s is found to produce maximum sperm motility by controlling the homeostasis of reactive oxygen species and boosting the release of adenosine triphosphate and respiratory enzyme activity in the mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…Recent studies have proposed cold plasma as a tool to enhance the production yield in chicken farms, through vaccine production, growth and reproduction enhancement (Wang; et al., ; Zhang et al., ; Zhang, Do, et al., ; Zhang, Huynh, et al., ; Zhang, Wang, et al., ), and to assure the safety of the poultry products (Aly, ; Apostol et al., ; Dirks et al., ; Georgescu et al., ; Lee et al., 2011, , ; Ragni et al., ; Rossow et al., ; Wang et al., ; Yong et al., ; Figure ). This wide range of potential application is because of the presence of reactive species and photons and the consequent chemical reactions that these components may induce in the treated product.…”
Section: Nonthermal Plasma and Poultry Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have proposed cold plasma as a tool to enhance the production yield in chicken farms, through vaccine production, growth and reproduction enhancement (Wang; et al., ; Zhang et al., ; Zhang, Do, et al., ; Zhang, Huynh, et al., ; Zhang, Wang, et al., ), and to assure the safety of the poultry products (Aly, ; Apostol et al., ; Dirks et al., ; Georgescu et al., ; Lee et al., 2011, , ; Ragni et al., ; Rossow et al., ; Wang et al., ; Yong et al., ; Figure ). This wide range of potential application is because of the presence of reactive species and photons and the consequent chemical reactions that these components may induce in the treated product.…”
Section: Nonthermal Plasma and Poultry Industrymentioning
confidence: 99%
“…Recently, the findings of many studies imply that nonthermal plasma technology can be considered a profitable tool in agri‐food industries such as the poultry industry. Researchers around the world showed that this emerging technology can be used for enhancing the microbiological safety of various products (Aly, ; Apostol, Georgescu, Vatuiu, & Gaceu, ; Dirks et al., ; Georgescu, Nicolae, Apostol, & Gherendi, ; Lee et al., , , ; Ragni et al., ; Rossow, Ludewig, & Braun, ; Wang, Zhuang, Lawrence, & Zhang., ; Yong et al., ) and increasing the production rates in the farm (Wang et al., ; Zhang et al., ; Zhang, Do, et al., ; Zhang, Huynh, et al., ; Zhang, Wang, et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Low and physiological concentrations of ROS stimulate sperm capacitation and acrosome reaction to ensure fertilization [89,93], but high concentrations of ROS lead to sperm DNA damage, impaired acrosome integrity, and decreased motility, viability, and fertilization capacity [92,94,95]. Zhang et al [21] reported that the appropriate treatment condition of non-thermal DBD plasma increased the chicken sperm motility in vitro by controlling the ROS balance and increasing the ATP level and respiratory enzyme activity in the mitochondria; this resulted from the regulation of the demethylation levels of genes involved in antioxidant defense and energetic metabolism [21]. Sperm DNA methylation levels are associated with sperm motility, but not with sperm viability or morphology [96].…”
Section: Plasma Improves Male Chicken Fertilitymentioning
confidence: 99%
“…Our laboratory has already developed a non-thermal DBD plasma treatment system at an atmospheric pressure to generate electrically safe plasma [17][18][19][20][21][22]. In brief, the DBD plasma reactor consists of upper and lower disk-shaped electrodes with a diameter of 140 mm and a dielectric barrier with a thickness of 5 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation